Pancasila, Hukum Konstitusi, dan Realitas Kawin Lari dalam Masyarakat : Pancasila, Constitutional Law, and the Reality of Eloping in Society - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Annisa Azka Faizah Azzahra; Hana Aulia Sukamto; Zaskia Azkazikra Azzahra (Litera Academica Publishing, 2024)
Pancasila, as the foundation of the Indonesian state, provides a philosophical and ethical framework for the administration of law and social life in the country. In the context of constitutional law, Pancasila serves as the highest source of law that guides lawmaking and regulatory interpretation. However, the implementation of Pancasila in law is not always in line with the social realities that occur in society, such as the phenomenon of elopement. Kawin lari, which is a marriage performed without going through official procedures or family permission, often reflects the misalignment between social norms, legal practices and socio- economic conditions of society. In Indonesian society, elopement can be considered an act that violates the legal provisions of marriage, which require official registration and consent from the relevant parties. However, in practice, elopement is often caused by factors such as social pressure, economic necessity or gender inequality. This phenomenon suggests an urgent need for harmonization between the principles of Pancasila and the application of constitutional law as well as policy adjustments that are more responsive to the social dynamics of society. This research aims to explore the relationship between Pancasila, constitutional law, and the reality of elopement in Indonesian society by analyzing the various legal and social dimensions of the phenomenon. The results are expected to provide insights into how the country’s fundamental principles can be more effectively integrated in legal practice as well as how legal reform can address existing social challenges.